2019
DOI: 10.48550/arxiv.1907.12611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smallest Fullerene-like Structures of Boron with Cr, Mo, and W Encapsulation

Amol B. Rahane,
Pinaki Saha,
N. Sukumar
et al.

Abstract: Using density functional theory calculations, we study doping of a Cr, Mo, and W atom in boron clusters in the size range of 18-24 atoms and report the finding of metal atom encapsulated fullerene-like cage structures with 20 to 24 boron atoms in contrast to a fullerene-like structure of pure boron with 40 atoms. Our results show that bicapped drum-shaped structures are favoured for neutral Cr@B 18 , Mo@B 20 , and W@B 20 clusters whereas a drum-shaped structure is preferred for neutral, cation, and anion of Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…331 Interestingly, the central Ta atom inside the [Ta@ B 28 ] 3+ cage interacts with 28 B atoms, which is the highest coordination number in the spherical environment known in chemistry. A detailed ab initio study of Cr, Mo, and W doping has also been carried out for B n clusters with n = 18, 20, 22, and 24 by Rahane et al 332 It has been shown that a drumshaped structure is favored for MB 18 (M = Mo, W), while a bicapped drum is favored for CrB 18 (B 16 drum) and MB 20 (M = Mo, W; B 18 drum). Also, a cage structure has been obtained for Cr@B 20 , M@B 22 , and M@B 24 for M = Cr, Mo, and W. Similar to the results by Lv et al, 60 the Cr@B 24 cage is distorted with some of the Cr−B bonds being elongated and the endohedral Cr atom does not interact with all the boron atoms strongly.…”
Section: Endohedrally Doped Carbon and Boron Fullerene Cagesmentioning
confidence: 99%
“…331 Interestingly, the central Ta atom inside the [Ta@ B 28 ] 3+ cage interacts with 28 B atoms, which is the highest coordination number in the spherical environment known in chemistry. A detailed ab initio study of Cr, Mo, and W doping has also been carried out for B n clusters with n = 18, 20, 22, and 24 by Rahane et al 332 It has been shown that a drumshaped structure is favored for MB 18 (M = Mo, W), while a bicapped drum is favored for CrB 18 (B 16 drum) and MB 20 (M = Mo, W; B 18 drum). Also, a cage structure has been obtained for Cr@B 20 , M@B 22 , and M@B 24 for M = Cr, Mo, and W. Similar to the results by Lv et al, 60 the Cr@B 24 cage is distorted with some of the Cr−B bonds being elongated and the endohedral Cr atom does not interact with all the boron atoms strongly.…”
Section: Endohedrally Doped Carbon and Boron Fullerene Cagesmentioning
confidence: 99%